Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1155/2019/6076571
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Scedosporiosis Induces Cerebral Oedema Associated with Abscess regarding Aquaporin-4 and Nrf-2 Depletions

Abstract: Cerebral involvement especially brain abscess is life-threatening complication and major cause of death during Scedosporium apiospermum infection. However, little is known about pathogenesis of brain oedema associated with abscess in scedosporiosis. Experimental scedosporiosis was conducted in BALB/cMlac mice to characterize the presence of brain oedema, its type, and its related mechanisms focusing on aquaporin (AQP)-4, nuclear factor erythroid-2 related factor (Nrf-2), and tumor necrotic factor (TNF)-α. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Elevation of tumor necrotic factor-α and downregulation of aquaporin-4 and nuclear factor erythroid-2 related factor in neuronal cells and myelin degeneration induced by S. apiospermum were found in non-treated mice, proposing the cause of water imbalance and oxidative stress which lead to cerebral edema and abscess. 29 Thus, our results proposed that a pre-coating catheter with TOH lessens the risk of cerebral and pulmonary complications due to S. apiospermum catheter-related infection.…”
Section: Dovepressmentioning
confidence: 60%
See 1 more Smart Citation
“…Elevation of tumor necrotic factor-α and downregulation of aquaporin-4 and nuclear factor erythroid-2 related factor in neuronal cells and myelin degeneration induced by S. apiospermum were found in non-treated mice, proposing the cause of water imbalance and oxidative stress which lead to cerebral edema and abscess. 29 Thus, our results proposed that a pre-coating catheter with TOH lessens the risk of cerebral and pulmonary complications due to S. apiospermum catheter-related infection.…”
Section: Dovepressmentioning
confidence: 60%
“…Overall, the histopathologic score was calculated by the combination of each histological change. 29…”
Section: Histopathology Analysismentioning
confidence: 99%
“…Recently, we reported cerebral edema associated with abscess after S. apiospermum infection. We showed that brain pathology resulted from the depletion of aquaporin (AQP)-4 expression [ 32 ]. AQP-4 is a water homeostasis membrane protein that plays an essential role in regulating water movement in the brain [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…To demonstrate the resolutive, antioxidative and immunomodulatory properties of the extract on both artificial and rat psoriasis skin specimens, the immunostaining, as described in our recent studies 30 35 , 38 , 39 , of caspase-3, nuclear factor erythroid 2-related factor (Nrf)-2, interleukin (IL)-10, TGF-β, β-defensin and CCL-20 were performed using rabbit isotype polyclonal antibodies (MyBioSource, USA). After deparaffinisation and dehydration, the antigenicity of the section was enhanced using heated citrate buffer (pH 6.0).…”
Section: Methodsmentioning
confidence: 99%